Avaliação semanal dos receptores de estrogênio α e progesterona no epitéllio mamário de mulheres após o uso de anticoncepcional hormonal combinado oral por um mês - Araujo Neto, Joaquim Teodoro De [UNIFESP] (2020)
Introduction: Oral combined contraceptives (OCC) have been used since 1957 and currently estimates that approximately one billion women worldwide use OCC to treat some gynecological disorders and primarily as a contraceptive method. Due to their systemic actions, OCC have benefits and harms. However it is the increased risk of breast cancer its most controversial adverse effect and the most feared by women. The mechanisms by which contraceptives would act on the breast parenchyma leading to its increased incidence, are not yet well known. Objectives: To calculate and compare α estrogen receptor (ERα) and progesterone receptor (PR) expression in the mammary epithelium in the first, second, third and fourth weeks of patients who do not use OCC (natural cycle) and those who use one cycle of OCC composed of 30 μg ethinyl estradiol (EE) and 150 μg levonorgestrel (L). Casuistic and Methods: A retrospective study with paraffin blocks of 118 women from February 2001 to February 2004. At the time, women were included in the menacme who had a breast lump with the triple diagnosis of positive benignity and eumenorrheic during the last six months. The study project was analyzed and approved by the Research Ethics Committee of UNIFESP-EPM. The patients underwent excision of the breast lumps and adjacent normal breast tissue fragments which were fixed in 10% buffered formalin. 31 patients were excluded and 87 patients were analyzed. The patients were divided into two groups: group A (with OCC) consisted of 42 women who used an OCC cycle composed of 30 μg of EE and 150 μg of L, group B (without OCC) consisted of 45 women with natural cycles. The immunohistochemical reaction was performed in an automation device and the following antibodies were used: ERα antibody clone SP1 titer 1:500 and PR antibody clone PgR636 titer 1:400. The histological slides were read using conventional optical microscopy. After identifying the epithelial areas, 7 fields with 40X magnification were evaluated. Statistical analysis for parity was performed using Fisher's exact test. At age the Students t-Test was applied. ERα and PR counts were evaluated in the Generalized Estimation Equation (EEG) model. In order to compare the total ERα and PR counts by evaluation and group moments, we used the Analysis of Variance (ANOVA) and the Kolmogorov-Smirnov test. Statistical analyzes were performed using the programs SPSS 20.0 and STATA 12. For all statistical tests the significance level of 5% (p ≤ 0.05) was adopted. Results: The control group (without OCC) had a higher mean age of 23.7 ± 5.9 years compared to the study group (with OCC) with a mean age of 20.5 ± 5.1 years. Regarding parity, the study group (with COC) had 83.9% of nulligesta versus 73.3% in the control group (without OCC). From the EEG model a statistically significant mean difference in ERα expression was observed in the fourth week in the study group (with COC) compared to the control group (without OCC) with p <0.001. The comparison of PR expressions in the control group (without OCC) in the fourth week or in the late luteal phase (LLP) with the ERα expressions, also in the fourth week (LLP) of the control group (without OCC) the mean PR expression was higher and statistically significant than ERα expression with p <0.001. The group of women using OCC showed higher average percentages of ERα (p <0.001) and PR (p <0.001) when compared to women in the control group (without OCC). Conclusions: The expressions of ERα and PR in users of an OCC cycle composed of 30 μg EE and 150 μg L higher percentages of ERα (p <0.001) and PR (p <0.001) media when compared to women from the control group (without OCC). The ERα expression in the study group (with OCC) in the fourth week (pause) was higher than the ERα expression in the fourth week (LLP) of the control group (without OCC), a statistically significant difference (p <0.001). The expression PR in the fourth week of the control group (without OCC) or LLP was higher than the ERα and this difference was statistically 5 significant (p <0.001). This difference was not observed at another three weeks in the control group (without OCC) and in the four weeks of the study group (with OCC).